斯里兰卡高中汉语教师职业选择与工作满意度的实证研究 - T.K.A.P. Kumara; M.M.N. Madhushika (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
With the growing interactions between China and Sri Lanka, the Sri Lankan government has placed increasing emphasis on Chinese language education, leading to a significant recruitment of high school Chinese language teachers. This study investigates the occupational motivation and job satisfaction of in-service Chinese language teachers in Sri Lankan high schools. A total of 120 teachers who participated in a seminar were surveyed, among whom 72 valid responses were collected. Adopting a mixed-methods approach, the study combined quantitative and qualitative analyses. Quantitative data, obtained through questionnaires, were analyzed using descriptive statistics to identify frequencies and percentages, while qualitative data were examined through coding and thematic analysis. The results indicate that most teachers entered the profession voluntarily and expressed overall satisfaction with their jobs, though a considerable number reported an intention to change careers. Stability of employment benefits was identified as a major factor in career choice. Among teachers fully committed to teaching, fewer than half expressed genuine passion for the profession. Based on these findings, the study recommends offering professional training and development opportunities, raising salaries, and enhancing societal recognition of teachers to improve motivation and job satisfaction.